Harnessing natural-product-inspired combinatorial chemistry and computation-guided synthesis to develop N-glycan modulators as anticancer agents. Issue 21 (4th May 2022) - Chen, Wei-An; Chen, Yu-Hsin; Hsieh, Chiao-Yun; Hung, Pi-Fang; Chen, Chiao-Wen; Chen, Chien-Hung; Lin, Jung-Lee; Cheng, Ting-Jen R.; Hsu, Tsui-Ling; Wu, Ying-Ta; Shen, Chia-Ning; Cheng, Wei-Chieh
Abstract : An integrated strategy of Natural-Product-Inspired Combinatorial Chemistry (NPICC) and Computation-Guided Synthesis is used to develop an α-hGMII inhibitor with 106-fold selectivity over α-hLM, with inhibitory effect on hepatocellular carcinoma. Abstract : Modulation of N -glycosylation using human Golgi α-mannosidase II (α-hGMII) inhibitors is a potential anticancer approach, but the clinical utility of current α-hGMII inhibitors is limited by their co-inhibition of human lysosomal α-mannosidase (α-hLM), resulting in abnormal storage of oligomannoses. We describe the synthesis and screening of a small library of novel bicyclic iminosugar-based scaffolds, prepared via natural product-inspired combinatorial chemistry (NPICC), which resulted in the identification of a primary α-hGMII inhibitor with 13.5-fold selectivity over α-hLM. Derivatization of this primary inhibitor using computation-guided synthesis (CGS) yielded an advanced α-hGMII inhibitor with nanomolar potency and 106-fold selectivity over α-hLM. In vitro studies demonstrated its N -glycan modulation and inhibitory effect on hepatocellular carcinoma (HCC) cells. In vivo studies confirmed its encouraging anti-HCC activity, without evidence of oligomannose accumulation.